Legal and Human Rights Violations in the Hajj Quota Diversion Policy in Indonesia - Lailatul Qadariyah; Umar Faruq (At-Tafkir, 2025)
The restructuring of Hajj quota distribution in Indonesia has generated concerns regarding its alignment with human rights standards, particularly principles of equality, justice, and non-discrimination. Yet, scholarly assessment of these issues remains limited, creating a research gap in understanding the legal and human rights implications of the quota transfer policy. This study aims to critically examine whether Indonesia’s Hajj quota transition policy constitutes a violation of domestic law and human rights norms. Employing a normative juridical method, the research utilizes a statutory and case-based approach, focusing on Law No. 8/2019 on the Implementation of Hajj and Umrah and other relevant regulations. The findings reveal that the Ministry of Religious Affairs’ quota transfer mechanism is inconsistent with the governing legal framework and fails to uphold human rights principles of equality and justice. The study highlights the need for future quota allocation policies to ensure strict legal compliance, transparency, and the protection of fundamental rights, thereby promoting a more equitable and accountable Hajj management system.